APLIKASI METODE CAPITAL ASSET PRICING MODEL (CAPM) DALAM MEMPREDIKSI RETURN SAHAM YANG TERGABUNG DALAM INDEKS KOMPAS 100 PERIODE 2017-2021 - Eva Azzahra; Muhammad Fuad; Dias Setianingsih (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2023)
This research aims to predict stock return using the Capital Asset Pricing Model (CAPM) method on stocks listed in the Compass100 Index for the period 2017-2021. This research population is companies listed in the Compass Index100 period February s.d July 2017. Sampling techniques with purposive sampling and obtained samples of 56 companies consistently listed in the Kompas100 Index period 2017-2021. This research is done by selecting efficient stocks. This study resulted that between beta and expected return there is an inverse relative relationship, so where the beta value is high then the share return rate will be low, as well as vice versa. Out of the 56 companies included in the survey, 31 are in efficient conditions and the remaining 25 are in inefficient conditions from 2017-2021. As for some factors that determine the classification is by comparing between Ri and E(Ri), if Ri > E(Ri) then the shares will be grouped into effective shares (undervalued) but instead if Ri < E(Ri) then those shares are grouped in ineffective shares. (overvalued). And if the results of the E(Ri) analysis show that the stock is efficient, then it is best for investors to buy or hold the stock to be used as an investment portfolio.